Sticky information Phillips curve with time-varying inattention - Correia, Henrique Danyi da Silveira (2023)
Inflation persistence is a pivotal topic in macroeconomic policy discussions. The Sticky Information Phillips Curve (SIPC) incorporates inflation persistence in a microfounded approach as a result of inattention from firms. Previous empirical analyses of the SIPC estimated inattention as constant in time, but this need not be the case. We review the canonical model of the SIPC to allow for time-varying inattention and present empirical evidence to support it. We also find that inattention in the SIPC is heavily associated with inflation volatility, as predicted by the Reis (2006a).